PERUBAHAN ORGANISASI DARI PERSPEKTIF MANAJEMEN SUMBER DAYA MANUSIA DALAM JURNAL TERINDEKS SCOPUS: ANALISIS BIBLIOMETRIK - Arbi Abdul Kahfi; Nurillah Jamil Achmawati Novel (JURNAL LENTERA BISNIS, 2024)
The aim of this study is to advance knowledge of organizational change research trends from a human resource management perspective using the Scopus database and bibliometric research. Analysis was conducted to look at the trend of publications between 1977 and 2021; using author, journal, country, subject, research institute/university, and various keywords related to organizational justice as search terms. 401 research articles became the source of data analysis. The results showed that the number of publications on the results of research on this topic in Scopus in 2006-2022 experienced a significant increase. In the realm of organizational change from the perspective of human resource management, change management is the most frequently used keyword. Human resource management functions were found to be still slightly associated with organizational changes that occurred. With these findings, it will help the development of future research.